Pengenalan Macam -Macam Perkembangan dan Karakteristik Anak di Desa Sebuntal Marang Kayu - Nurul Hikmah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
Development is change that is owned by humans. Development is also a process through which to reach adulthood. The problems that occur in children in Sebuntal Marang Kayu Village are: the development and character of children is very worrying or worrying. This can be seen in the daily activities of children at school and at home that do not show good character. The purpose of this activity is to disseminate information in the field of education, provide information and knowledge to parents and children, related to child development. The result of this community service activity is that the activities can run smoothly. This activity received a friendly welcome, there was evidence that many participants were present, active, remained at the activity location until it was finished. This activity is useful in providing cognitive aspects and deeper understanding. This activity is a motivation for mothers, fathers and children in monitoring their children's attitudes. So, this activity is the most important part of increasing awareness for the community in guiding children's development.